Upaya Usaha Mikro Kecil Menengah (UMKM) Terhadap Kesejahtreraan Masyarakat Dalam Perspektif Ekonomi Syariah Desa Sipispis Kecamatan Sipispis Kabupaten Serdang Bedagai - Damanik, Azhari Firnanda; Effendi, Syamsul; Rahman, Abdul (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2025)
MSMEs (Micro, Small and Medium Enterprises) are independent productive business units, carried out by individuals or business entities in all economic sectors. In principle, the distinction between micro, small, medium, and large businesses is generally based on the initial asset value (excluding land and buildings), average annual turnover, or number of permanent workers. The purpose of this study is to determine the impact of Micro, Small and Medium Enterprises (MSMEs) on Community Welfare in the Perspective of Islamic Economics in Sipispis Village, Sipispis District, Serdang Bedagai Regency. To determine the pattern of Micro, Small and Medium Enterprises (MSMEs) on Community Welfare in the Perspective of Islamic Economics in Sipispis Village, Sipispis District, Serdang Bedagai Regency. To determine the implementation of wage payments for Micro, Small and Medium Enterprises (MSMEs) on Community Welfare in the Perspective of Islamic Economics in Sipispis Village, Sipispis District, Serdang Bedagai Regency. The method used in this study is quantitative. It is called Quantitative because the data collected in this study can be analyzed using statistical analysis.